Tata Kelola Kebijakan Kota Layak Anak Pada Klaster Kesehatan dan Kesejahteraan di Kota Cilegon - Prafitri, Nikki; Rizkiyani, Tiwi; Rahayu, Sierfi (FIA Unkris Press, 2025)
Governance is an interaction between stakeholders in meeting the interests of the community. The fulfillment of children's rights, especially in the health sector, requires the application of optimal governance principles. The implementation of Child-Friendly Cities in Cilegon City in the child health and welfare cluster still shows governance that is not optimal in some indicators. The problems that still occur include the uneven availability of lactation room facilities in public facilities, uneven clean water facilities and the ineffectiveness of the implementation of the No Smoking Area.The purpose of this study is to determine the governance of the Child-Friendly City policy in the health and welfare cluster in Cilegon City. The method used is a qualitative research method. The results of the study show that the governance of the Child-Friendly City policy in the health and welfare cluster has been well managed, although optimization of each indicator is still needed. This is because there are still many indicators in the cluster that have not reached the optimal score in the assessment of Child-Friendly City. The governance of the Child-Friendly City policy in the health and welfare cluster in Cilegon City can run well supported by local government initiatives in realizing participation between parties, face-to-face dialogue on the aspect of transparency, cooperation to optimize accountability and coordination, and monitoring to increase responsiveness in implementing health and welfare cluster support programs.